Development of Interactive E-Modules Based on Problem Based Learning on the Material of Human Sight and Hearing Senses - Berliana, Chyntia; Andriani, Aldina Eka (Jurnal Pijar Mipa, 2025)
The limited variety of stimuli and problem-solving activities in teaching materials causes low learning outcomes for students. This study aims to describe the development design, test the feasibility and effectiveness of Interactive E-Modules based on Problem-Based Learning to improve student learning outcomes on the material of the senses of human vision and hearing in class IV SDN Kalibanteng Kidul 03 Semarang City. The type of research used is Research and Development (R&D) with the Borg and Gall model. The research subjects were fourth-grade students of SDN Kalibanteng Kidul 03, which amounted to 23 students. Data collection techniques using tests (pretest and posttest) and non-tests (observation, interviews, questionnaires and document data). Data analysis techniques used normality test, t-test, and N-Gain test. The results showed that the development design of interactive E-Modules based on Problem Based Learning using the Canva application consisted of the main page, instructions for use and activities, table of contents, learning outcomes and objectives, concept maps, learning materials based on Problem Based Learning syntax, visual media in the form of 3D images using (Assemblr EDU), learning videos, glossary, interactive quizzes (Wordwall), bibliography and developer profile. The feasibility of interactive E-Modules based on Problem-Based Learning from material experts, 92.5% of the criteria are very feasible, and media experts, 90% of the criteria are very feasible, supported by the results of the teacher response questionnaire, 95% with very feasible criteria and 100% of student responses with very feasible criteria. The effectiveness of interactive E-Modules based on Problem Based Learning is shown from the increase in pre-test and post-test scores by 39.3, this result is supported by the results of the t-test showing a significance value (2-tailed) <0.000 which based on the criteria the value is below 0.05 and the results of the N-gain test of 0.6706 medium criteria. The conclusion of this study shows that the interactive E-Module based on Problem-Based Learning was successfully developed, very feasible, and effective for improving the learning outcomes of the material of the senses of vision and human hearing in fourth-grade students of SDN Kalibanteng Kidul 03, Semarang City.